Recovering Marx’s Theory of Alienation: Theoretical Considerations from a Case Study with Community Activists in Scarborough, Ontario - Sawan, Joseph E (Just Labour, 2011)
The expansive literature on alienation demonstrates how various treatments emphasize different parts of human estrangement. This recovery focuses on demonstrating how Marx’s theory of alienation can prove fruitful in understanding social movement activity and promoting social justice. At the centre of collective action is a hope and vision for an alternative future, an imagination of communities based on mutual reliance and a strategy for de-alienation. In this paper, I begin with a review of Marx’s theory with an emphasis on a philosophy of internal relations, followed by an application to a recently completed case study with housing activists in Scarborough, Ontario. By posing questions for further development, I conclude that social alienation and responses to it can be developed further when seen as a learning process; that is, to understand the learning processes of one’s own estrangement as central to taking positive steps to overcome alienation.